Groklaw – Where We Have Been and Where We Are Going (Journal of Open Law, Technology & Society, 2011)
After 8 years documenting litigation, explaining complicated legal matters and debunking uncertainty in the field of FOSS, Pamela Jones passed the baton on the Groklaw.net news website over to Mark Webbink. Under his editorship, Groklaw 2.0 will remain committed to its values and accuracy in reporting, though it will increasingly engage with issues like patent litigation to reflect current market tensions and imperatives.